DETERMINANTS OF ENERGY DEPENDENCY IN ASIA: THE MODERATING ROLE OF GEOPOLITICAL RISK IN THE FOREIGN DIRECT INVESTMENT-ENERGY NEXUS - Kaukab, M Elfan; Sasmito, Agus Pulung (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study aims to identify the determinants of energy dependency in Asia and examine whether geopolitical risk moderates the relationship between foreign direct investment (FDI) and energy dependency. Using secondary data from the International Energy Agency (IEA), the United States Energy Information Agency (EIA), the World Bank, the United Nations Trade and Development, and the Geopolitical Risk Index database, the study analyzes 77 observations from 27 Asian countries covering 2014, 2018, and 2022. Tobit regression is employed as the primary estimation method because energy dependency is bounded between 0 and 1, while fractional logit and fixed-effects panel regressions are used as robustness checks. The results indicate that geopolitical risk, institutional quality, carbon emissions per capita, and the interaction between FDI and geopolitical risk significantly influence energy dependency in the Tobit model. The interaction effect indicates that FDI is more effective at reducing energy dependency under higher geopolitical risk conditions. Fixed-effects estimation further shows that fossil fuel reliance is a significant determinant of energy dependency over time. Such divergence underscores the importance of model specification and provides a more nuanced understanding of the factors driving energy dependency. This study contributes to the energy security literature by extends resource dependency theory and shows that the determinants of energy dependency differ between structural cross-country conditions and within-country temporal dynamics. The novelty of this research is the moderating role of geopolitical risk in the relationship between FDI and energy dependency.